To find any association of maternal blood group as a risk factor for preeclampsia - Mital, Premlata; Gupta, Divya; Benwal, Devendra Kumar; Gangwal, Himanshi; Hooja, Nupur; Agarwal, Suchita; Ainani, Richa (International Journal Of Community Medicine And Public Health, 2016)
Background: Preeclampsia, a multisystem disorder, one of the three leading causes of maternal morbidity and mortality worldwide. Various risk factors have been identified for its development. Recently ABO blood group has been related to risk of preeclampsia. Aims and Objective: to investigate any possible relationship between the ABO/Rh blood group system and preeclampsia. Methods: 250 pregnant women with Rh positive blood group, who were fulfilling the criteria for preeclampsia were selected as cases and 250 women with normal pregnancy without any complications, with Rh positive blood group, were selected as controls. Odd ratio was calculated to find the correlation of the patients with preeclampsia and control group from the point of ABO blood groups. Results: Blood group AB has the highest, and O has lowest risk for preeclampsia among the ABO blood groups. Out of 41 women with severe pre-eclampsia, most of them (39.0) had blood group AB and there was a significant difference between the patients with severe preeclampsia, mild preeclampsia and control group in terms of distribution of ABO blood groups. Conclusions: It was observed that women with AB blood group are at higher risk. So to prevent the PIH and improve the prognosis ABO blood groups of each pregnant women should be done in first trimester and special attention should be given to women with AB blood group.